Effects of 10-weeks additional proprioceptive training on balance and joints functional stability of young sprinters - Bajramovic, I.; Alic, H.; Likis, S.; Manic, G. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The aim of this research is to determine efficiency of 10-week additional proprioceptive training on balance and joints functional stability of young sprinters. Presented program is constructed as an addition to regular training in athletic sprint. Sample subjects of this research were 10 young sprinters aged from 13 to 17. Biodex Balance System and variables: Over Stability Index (OSI), Anterior/Posterior Stability Index (APSI) i Medial/Lateral Stability Index (MLSI) were used for assessment of efficiency and balance of functional stability of joints. Proprioceptive program was performed at the beginning of training. T test (Paired Samples Test) showed statistically significant differences in all three variables (p<.01). It can be concluded that additional proprioceptive training constructed as an addition to regular athletic sprint training contributes to the balance and functional stability of joints of lower limbs. Also with this training is possible to improve coordination and precision of movements, speed of reflexes and dynamics of joints. It is also recommended that proprioceptive training is used at the beginning of training (after warm-up) and during the process of sport preparation.